2019
DOI: 10.1038/s41598-019-51072-5
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation of living coral embryos and larvae

Abstract: Embedding and immobilisation of living cells and microorganisms is used in a variety of research and commercial applications. Here we report the successful extended immobilisation of coral larvae in a low-gelling temperature agarose. Embryos and larvae of five broadcast-spawning Scleractinian species were immobilised in agarose gel and tested in a series of exploratory survival and settlement assays. The optimal developmental stage for immobilisation was after ciliation at approximately 24 hours post-fertilisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Large-particle flow cytometry has also been applied to the screening and sorting of microencapsulated particles, cells, and organisms, such as fungal spores encapsulated in calcium alginate beads 18 . A recent investigation that immobilised several species of coral propagules in an agarose gel found that survival of immobilised larvae was high, and that the encapsulation process did not significantly impede larval settlement after immobilisation 42 . A work flow could be developed whereby the output from automated encapsulation feeds directly into a large-particle flow cytometer to measure and sort individually-encapsulated particles.…”
Section: Discussionmentioning
confidence: 98%
“…Large-particle flow cytometry has also been applied to the screening and sorting of microencapsulated particles, cells, and organisms, such as fungal spores encapsulated in calcium alginate beads 18 . A recent investigation that immobilised several species of coral propagules in an agarose gel found that survival of immobilised larvae was high, and that the encapsulation process did not significantly impede larval settlement after immobilisation 42 . A work flow could be developed whereby the output from automated encapsulation feeds directly into a large-particle flow cytometer to measure and sort individually-encapsulated particles.…”
Section: Discussionmentioning
confidence: 98%
“…Coral planulae have been studied to understand the skeletogenesis in scleractinians (le Tissier, 1988) and the effects of factors such as pollution (Rinkevich and Loya, 1979). Studies have also tested new biotechnology for coral reef research and restoration (Randall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mechanisms that improve coral recruitment (i.e., survivorship rates of recruitment) could be an important research frontier to enhance coral population recovery after disturbance. Examples include innovations in new materials (e.g., hydrogels) to protect corals in vulnerable early life stages and increase survivorship of coral recruits (Randall et al, 2019), the incorporation of crustose coralline algae and biofilms in restoration projects (Heyward & Negri, 1999), or the use of acoustic playback of a healthy reef to enhance coral settlement in degraded sites (Gordon et al, 2019; Lillis et al, 2016).…”
Section: Future Directionsmentioning
confidence: 99%